2021
DOI: 10.1001/jamanetworkopen.2021.11369
|View full text |Cite
|
Sign up to set email alerts
|

Bilateral Chilblain-like Lesions of the Toes Characterized by Microvascular Remodeling in Adolescents During the COVID-19 Pandemic

Abstract: IMPORTANCE Chilblain-like lesions have been one of the most frequently described cutaneous manifestations during the COVID-19 pandemic. Their etiopathogenesis, including the role of SARS-CoV-2, remains elusive. OBJECTIVE To examine the association of chilblain-like lesions with SARS-CoV-2 infection. DESIGN, SETTING, AND PARTICIPANTS This prospective case series enrolled 17 adolescents who presented with chilblain-like lesions from April 1 to June 30, 2020, at a tertiary referral academic hospital in Italy. MAI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
44
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(46 citation statements)
references
References 50 publications
2
44
0
Order By: Relevance
“…In this detailed study of a cohort of patients with chilblain eruptions presumed to be caused by SARS-CoV-2, we do not find evidence supporting an association with prior infection. Many observational reports have offered circumstantial evidence pointing toward an association with SARS-CoV-2 infection, although the immunological and PCR data have been more limited, with only the minority of cases having evidence of infection ( 1 , 4 8 ) and some studies having none whatsoever ( 2 , 3 , 12 ). Importantly, PC cases are being diagnosed and managed differently than idiopathic chilblains due to this presumed relationship with SARS-CoV-2 ( 19 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this detailed study of a cohort of patients with chilblain eruptions presumed to be caused by SARS-CoV-2, we do not find evidence supporting an association with prior infection. Many observational reports have offered circumstantial evidence pointing toward an association with SARS-CoV-2 infection, although the immunological and PCR data have been more limited, with only the minority of cases having evidence of infection ( 1 , 4 8 ) and some studies having none whatsoever ( 2 , 3 , 12 ). Importantly, PC cases are being diagnosed and managed differently than idiopathic chilblains due to this presumed relationship with SARS-CoV-2 ( 19 ).…”
Section: Discussionmentioning
confidence: 99%
“…Despite this purported association between PC and SARS-CoV-2 infection, the majority of these patients lack evidence of prior infection ( 1 , 4 8 ). Although testing was not widely available in early studies, this relationship has nonetheless held in later studies with more comprehensive testing ( 2 , 3 , 12 ). Arguments for this persistent inability to detect prior infection include 1) a missed window, with PCR testing too late and antibody testing too early; 2) loss of antibody positivity over time; and 3) that PC patients may feature a robust SARS-CoV-2 innate immune response that impedes the development of a detectable antibody signal ( 13 ).…”
mentioning
confidence: 99%
“…While investigations to understand the pathophysiology of pandemic‐associated pernio continue, 16 , 17 , 18 , 19 evidence has shown that SARS‐CoV‐2 spike protein and robust IFN‐1 response are seen in the skin of patients with chilblains, suggesting an excessive innate immune skin response to SARS‐CoV‐2. These findings suggest IFN‐1 signaling may affect host outcomes to COVID‐19.…”
Section: Discussionmentioning
confidence: 99%
“…In these patients, a SARS‐CoV‐2 infection was excluded by in situ hybridization and serologic testing. 11 …”
Section: Nail Changes Induced By Sars‐cov ‐2 Infectionmentioning
confidence: 99%
“…In these patients, a SARS-CoV-2 infection was excluded by in situ hybridization and serologic testing. 11 Thirty-three patients (mean age 23.4 years) with chilblains during the COVD-19 pandemic presented with erythematous and purpuric papules on the toes or fingers with edema and pruritus or burning sensation. Histology (n = 5) revealed superficial dermal lymphocytic infiltrates around vessels and eccrine sweat glands.…”
Section: Covid-toe or -Fingermentioning
confidence: 99%